Hubungan Aktivitas Fisik dan Kualitas Tidur dengan Tekanan Darah pada Karyawan Universitas Swadaya Gunung Jati - Khasanah, Uswatun; Syah, Pangeran Akbar; Imaroh, Fadilatusyifa’ul (LPPM Universitas Respati Indonesia, 2025)
Background: Hypertension is a condition that affects the heart and circulatory system, often without symptoms, but can cause serious problems. Low physical activity and poor sleep quality can affect blood pressure. Aim: examining the relationship between physical activity, sleep quality, and blood pressure among employees at Gunung Jati University. Methods: This study is an observational study with a cross-sectional approach conducted on employees of Gunung Jati Cirebon University, involving 134 employees in May 2025 using consecutive sampling techniques and the GPAQ physical activity questionnaire and PSQI sleep questionnaire. Data analysis was performed by applying the Spearman correlation test. Results: Most of the physical activity of Gunung Jati Swadaya University employees falls into the moderate category, at 40.3%. The sleep quality of Gunung Jati Swadaya University employees is mostly poor, at 81.3%, and the blood pressure of employees at this university is mostly high normal, at 24.6%. Statistical analysis shows a significant relationship between physical activity and blood pressure, with a p-value of 0.000 and r = -0.370, and no significant relationship between sleep quality and blood pressure, with p = 0.108 and r = 0.139. Conclusion: There is a relationship between physical activity and blood pressure among employees at Gunung Jati Swadaya University, with a moderate correlation strength and a negative variable direction. The less physically active a person is, the higher their blood pressure. There is no correlation between sleep quality and blood pressure among employees at Gunung Jati Swadaya University.